Sedum kamtschaticum exerts hypnotic effects via adenosine A2A receptor in mice - 김연수 (The Graduate School, Ajou University, 2024)
Insomnia is a common sleep disorder with significant societal and economic impacts. Current pharmacotherapy often has unwanted side effects, necessitating the exploration for new therapeutic drugs. This research investigated the hypnotic effects and mechanisms of Sedum kamtschaticum 30% ethanol extract (ESK) and one of its active compounds myricitrin using pentobarbital-induced sleep experiments, immunohistochemistry (IHC), immunofluorescence (IF), receptor binding assay and ELISA assay in mice. Our results from the pentobarbital-induced sleep experiments, showed that ESK and myricitrin reduced sleep latency and prolonged total sleep time in a dose-dependent manner. The findings from c-Fos immunostaining indicated that ESK and myricitrin enhanced neural activity in sleep-promoting VLPO GABAergic. We also confirmed the level of GABA released from VLPO GABAergic neurons. ESK and myricitrin increased the release of GABA in the hypothalamus. All these effects were significantly inhibited by SCH. Additionally, ESK showed a concentration-dependent binding affinity to the adenosine A2A receptor (A2AR). In conclusion, ESK and myricitrin have hypnotic effects and the underlying mechanism may be related to the activation of A2AR.
학위논문(석사)--약학과,2024. 8
Keywords: Adenosine A2A receptor; GABAergic neuron; Hypnotic effect; Myricitrin; Sedum kamtschaticum